Training load and injury among middle school-aged athletes - Albrecht, J.; Biese, K. M.; Bell, R. D.; Schaefer, D. A.; Watson, A. M. (Journal of Athletic Training, 2020)
Context: Young athletes are encouraged to participate in high-intensity sport programs. However, most research on the association between training volume (TV) and injury has been performed on adult or professional athletes. Objective: To evaluate the association between acute and chronic TV (hours/week) and reported injury (yes/no) and evaluate the relationship between acute : chronic TV and injury while controlling for sex, age, and prior injury in young athletes. Design: Cohort study. Setting: Online surveys. Patients or Other Participants: Middle school-aged adolescents. Main Outcome Measure(s): We conducted a baseline survey at the start of the 2017-2018 academic year. The baseline survey solicited information regarding demographics, injury history, and primary sport. Subsequent surveys were delivered electronically at the start of each week. Information obtained with the weekly survey included weekly TV and injuries sustained the previous week. Injuries were reported and classified (eg, acute or gradual onset) by the participants. Weekly TV was aggregated as rolling averages over the prior 2, 3, and 4 weeks. Acute:chronic TV was calculated for each participant for every week as the prior week TV divided by the TV during the prior 2 (1 : 2), 3 (1 : 3), and 4 (1 : 4) weeks of the study period. Results: A total of 244 recruits participated. Higher average TV over the prior 4 weeks (odds ratio [OR] = 0.97; 95% confidence interval [CI] = 0.93, 1.00; P = .05) was associated with fewer reported injuries. Additionally, higher average TV over the prior 2 (OR = 0.96; 95% CI = 0.93, 0.99; P = .04), 3 (OR = 0.95; 95% CI = 0.91, 0.99; P = .02), and 4 (OR = 0.95; 95% CI = 0.91, 0.99; P = .05) weeks was associated with fewer reported acute injuries the following week. Acute:chronic TV and any injury type were not related. Conclusions: Consistent, higher levels of physical activity may offer protection against acute injury in young athletes.